Performance Analysis of Mining Companies Listed on the Indonesia Stock Exchange Before and During the Covid-19 Pandemic for the 2018-2021 Period - Suhatmi, Erna Chotidjah; Prastiwi, Putri Intan; Restiana, Della (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
The rapid development of the mining sector that occurred in Indonesia attracted the interest of investors to invest in the mining sector. This study aims to determine the financial performance of mining companies listed on the Indonesia Stock Exchange before and during the Covid-19 pandemic. The analytical method used is a quantitative descriptive method using the ratio of liquidity, solvency and profitability. The sampling technique is purposive sampling and uses secondary data in the form of the 2018-2021 annual financial reports from 3 companies in the mining sector, namely PT Bumi Resources Tbk, PT Adaro Energy Tbk, and PT Indika Energy Tbk. The results of the calculation of the liquidity ratio illustrate that the mining company that reached number 1, namely PT Adaro Energy Tbk. The calculation results of the solvency ratio illustrate that overall the company's condition is in a fairly good condition even though in 2020 the ratio has decreased. The results of the calculation of the profitability ratios illustrate that 3 mining companies are below the standard value of the ratio. The results of calculating the ratio of liquidity, solvency and profitability illustrate that the company's performance was said to be good before and during the Covid-19 pandemic, namely PT Adaro Energy Tbk.